Republic of Palau : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report, 2006)
This Selected Issues paper and Statistical Appendix describes Palau's financial sector, its recent performance, and developments in regulatory reform. The paper considers illustrative scenarios of possible outcomes for public spending levels and growth under different assumptions with respect to future grants and the long-term value of government assets held in the Compact Trust Fund. Sensitivity of the results to the rate of return on assets is considered. The paper also covers recent fiscal performance, revenue and expenditure reforms, and some financing issues.